Splenosis: a diagnosis to be considered - Ribeiro,Jorge C. (2006)
The term splenosis applies to the autotransplanted splenic tissue resulting from seeding in the context of past splenic trauma or surgery. We report a 42-year-old man with a history of splenectomy observed for an incidentally found retrovesical mass thought to be an ectopic testicle. The abdominal laparotomy revealed multiple focuses of pelvic splenosis. As splenosis can be diagnosed through specific imaging studies one should always consider it in differential diagnosis of a mass discovered years after splenic surgery or trauma.